Pleural invasion, epidermal growth factor receptor mutation and carcinoembryonic antigen level affect pleural lavage cytology-positive status in non-small-cell lung cancer. (16th November 2020) - Fujibayashi, Yusuke; Ogawa, Hiroyuki; Kitazume, Mai; Nishikubo, Megumi; Nishioka, Yuki; Kimura, Kenji; Tane, Shinya; Kitamura, Yoshitaka; Nishio, Wataru
Abstract:  : OBJECTIVES: Pleural invasion (pl) is strongly associated with the pleural lavage cytology (PLC) status. We analysed tumours with pl and evaluated the relationship between the PLC status and pl. METHODS: We retrospectively reviewed 428 surgically treated patients who had been diagnosed with non-small-cell lung cancer with pl and had their PLC status examined between 2000 and 2016. We investigated the influence of a PLC-positive status on the prognosis and searched for the factors predictive of a PLC-positive status. RESULTS: Seventy-eight (18%) patients were PLC positive. The recurrence-free survival of PLC-positive patients was significantly worse than that of PLC-negative patients in pl1 and pl2, but not in pl3 (5-year recurrence-free survival rate, PLC positive versus PLC negative: pl1, 22.0% vs 60.0%, P  = 0.002; pl2, 30.4% vs 59.7%, P  = 0.015; pl3, 50.0% vs 59.6%, P  = 0.427). A multivariable analysis showed that the degree of pl (pl2–3 versus pl1) [odds ratio (OR) 5.34, P  < 0.001] was an independent predictive factor for PLC positivity. Epidermal growth factor receptor (EGFR) mutation positivity (OR 5.48, P  = 0.042) and carcinoembryonic antigen (CEA) ≥5 ng/ml (OR 3.78, P  = 0.042) were associated with a PLC-positive status in patients with pl2–3. We found that the PLC-positive rate in patients with pl2–3 was 35.6%; however, if the tumour was EGFR mutation positive and had CEA ≥5 ng/ml, the PLC-positive rate increased to 77%. CONCLUSIONS: If a tumour was suspected of being pl2–3 and had EGFR mutation positivity and CEA ≥5 ng/ml, the PLC-positive rate was extremely high. Clinical trial registration number: Hyogo Cancer Center, G-138.